Carbohydrate Metabolism in Health and Disease - Javier T. Gonzalez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Carbohydrate metabolism is a fundamental aspect of health and a crucial function in a variety of species, including humans. A primary disfunction in major global diseases, such as cardiovascular disease and diabetes, is dysregulation of thecarbohydrate metabolism. Furthermore, certain disease outcomes may be impacted by the amount and type of dietary carbohydrates consumed. Finally, carbohydrate obtainability is essential for optimal performance and endurance during sporting events. This book collates articles that either describe original research, or review the scientific literature on the topic of carbohydrate metabolism in health and disease. .